2019
DOI: 10.13057/asianjfor/r030203
|View full text |Cite
|
Sign up to set email alerts
|

Review: Floral resources diversity and vegetation types important for honeybees in Ethiopia

Abstract: Abstract. Addi A, Bareke T. 2019. Review: Floral resources diversity and vegetation types important for honeybees in Ethiopia. Asian J For 3: 64-68. The high biodiversity of Ethiopia is attributed to its wide range of altitude and great geo-morphological diversity. This has resulted in the existence of a high diversity of floral resources of which majority of them are visited by honeybees. This paper aimed to review existing studies on bee floral resources in Ethiopia to understand the types of bee plants, flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 0 publications
3
12
0
Order By: Relevance
“…Similarly, information from Tesfaye et al [13] found that Guizotia from honey harvested in October-November accounted for 87% of total pollen counts. Our results are similar to Addi and Bareke [14], where G. scarba produced single-fower honey as it grows abundantly in diferent habitats, cultivated land, forest edges, and open grasslands.…”
Section: Honey Harvested In Novembersupporting
confidence: 88%
See 3 more Smart Citations
“…Similarly, information from Tesfaye et al [13] found that Guizotia from honey harvested in October-November accounted for 87% of total pollen counts. Our results are similar to Addi and Bareke [14], where G. scarba produced single-fower honey as it grows abundantly in diferent habitats, cultivated land, forest edges, and open grasslands.…”
Section: Honey Harvested In Novembersupporting
confidence: 88%
“…Of the 6 plant families identifed, the highest number of melliferous plant species were found under Myrtaceae (50.0% of total plant species recorded) that contributed a cumulative 53.41% of the total pollen grain weighed, while Asteraceae is the second rich plant family (33.3%) but least cumulative pollen trapped (0.19%). Comparable information was reported by Addi and Bareke [14] in the Gera forest, 60% of the pollen was counted from C. macrostachyus honey harvested at the end of the small rainy season in June. Te dominance of a monoforal species from a honey source in honey samples is determined by its abundance, nectar potential, and fowering schedule of the plant [15].…”
Section: Honey Harvested In Maysupporting
confidence: 62%
See 2 more Smart Citations
“…Moreover, the pollen shape study revealed that most of the plants displayed a spheroidal pollen shape with circular outline. The polar axis and equatorial diameter of pollen grain size ranges from 17.5-32.0 and 18.0-73.0 (Table 1 and Figure 2 shortly after the end of the main rainy season in most highlands of Ethiopia as reported by Addi and Bareke (2019).…”
Section: Botanical Originmentioning
confidence: 88%